The Interplay between the Hippocampus and Amygdala in Regulating Aberrant Hippocampal Neurogenesis during Protracted Abstinence from Alcohol Dependence - Mandyam, Chitra D. (Frontiers in Psychiatry, 2013)
The development of alcohol dependence involves elevated anxiety, low mood, and increased sensitivity to stress, collectively labeled negative affect. Particularly interesting is the recent accumulating evidence that sensitized extrahypothalamic stress systems [e.g., hyperglutamatergic activity, blunted hypothalamic-pituitary-adrenal (HPA) hormonal levels, altered corticotropin-releasing factor signaling, and altered glucocorticoid receptor signaling in the extended amygdala] are evident in withdrawn dependent rats, supporting the hypothesis that pathological neuroadaptations in the extended amygdala contribute to the negative affective state. Notably, hippocampal neurotoxicity observed as aberrant dentate gyrus (DG) neurogenesis (neurogenesis is a process where neural stem cells in the adult hippocampal subgranular zone generate DG granule cell neurons) and DG neurodegeneration are observed in withdrawn dependent rats. These correlations between withdrawal and aberrant neurogenesis in dependent rats suggest that alterations in the DG could be hypothesized to be due to compromised HPA axis activity and associated hyperglutamatergic activity originating from the basolateral amygdala in withdrawn dependent rats. This review discusses a possible link between the neuroadaptations in the extended amygdala stress systems and the resulting pathological plasticity that could facilitate recruitment of new emotional memory circuits in the hippocampus as a function of aberrant DG neurogenesis.